The hydrogen bond continuum in solid isonicotinic acid - Blahut, Jan; Štoček, Jakub Radek; Šála, Michal; Dračínský, Martin (Journal of magnetic resonance, 2022)
The understanding and correct description of intermolecular hydrogen bonds are crucial in the field of multicomponent pharmaceutical solids, such as salts and cocrystals. Solid isonicotinic acid can serve as a suitable model for the development of methods that can accurately characterize these hydrogen bonds. Experimental solid-state NMR has revealed a remarkable temperature dependence and deuterium-isotope-induced changes of the chemical shifts of the atoms involved in the intermolecular hydrogen bond; these NMR data are related to changes of the average position of the hydrogen atom. These changes of NMR parameters were interpreted using periodic DFT path-integral molecular dynamics (PIMD) simulations. The small size of the unit cell of isonicotinic acid allowed for PIMD simulations with the computationally demanding hybrid DFT functional. Calculations of NMR parameters based on the hybrid-functional PIMD simulations are in excellent agreement with experiment. It is thus demonstrated that an accurate characterization of intermolecular hydrogen bonds can be achieved by a combination of NMR experiments and advanced computations.
Keywords: kyseliny isonikotinové; vodíková vazba; Isonicotinic Acids; Hydrogen Bonding